Sources of roughage and milo for finishing steers - K. Bolsen; Jack G. Riley (Kansas Agricultural Experiment Station Research Reports, 1976)
One hundred five yearling steers were used to evaluate seven milo treatments: (1) dry, (2) micronized, (3) steam flaked +.2% propionic acid (acid-flake), (4) field harvested high moisture (F-HM) ensiled whole in an 02 -limiting silo, (5) F-HM rolled and ensiled in a concrete stave silo, (6) reconstituted, high moisture (R-HM) ensiled whole in an 02 -limiting silo and (7) R-HM rolled and ensiled in a concrete stave silo; and three roughages: (1) corn silage, (2) equal parts sorghum silage and milo stover silage and (3) milo stover pellets. The complete mixed rations fed during the 92-day trial were 80% milo, 15% roughage and 5% supplement. Steers fed micronized or acid-flake milo gained 16 and 20% more efficiently, respectively, than steers fed dry-rolled milo. Efficiencies of gain were similar for steers fed dry-rolled milo and those fed any one of the four high moisture milo treatments. Rates of gain and carcass characteristics were not significantly affected by milo treatment. Corn silage supported faster (P<.05) and more efficient (P<.05) gains than sorghum-mile stover silages or milo stover pellets.
Keywords: Cattlemen' s Day; 1976; Report of progress (Kansas State University. Agricultural Experiment Station); 262; Beef; Roughage; Milo; Finishing steers